Cushing Syndrome from Functioning Adrenal Adenoma in A Nigerian Woman: A Case Report - Mumini Rasheed; Nabila Ado Ya’u; Salisu Isma’il; Abdullah Abib; Najeem Idowu; Adebayo Adekunle; Kehinde Ademoye (AlQalam Journal of Medical and Applied Sciences, 2024)
Cushing syndrome is a clinical condition characterized by elevated body cortisol level with its attendant clinical features. It's relatively rare. We report this clinical condition due to its rarity and our objective was to illustrate the clinical features, diagnosis and the its successful management. A 23-year-old Nigerian woman was seen at the surgical outpatient department of federal medical centre Dutse, Jigawa State following a referral from the general outpatient department of the same institution with 2 years history of amenorrhea, excessive weight gain and hirsutism. The clinical examination was remarkable for raised blood pressure and Cushingoid appearance. Besides, biochemical and radiological evaluation were suggestive of right adrenal hypercortisolism. She had open right adrenalectomy and was discharged satisfactorily symptoms free with clinical follow that has been uneventful. We have reported our experience on the successful management of a rare case of Cushing syndrome secondary to adrenal adenoma. متلازمة كوشينغ هي حالة سريرية تتميز بارتفاع مستوى الكورتيزول في الجسم مع المظاهر السريرية المصاحبة له. إنه نادر نسبيًا. لقد قمنا بالإبلاغ عن هذه الحالة السريرية بسبب ندرتها وكان هدفنا هو توضيح المظاهر السريرية والتشخيص والإدارة الناجحة لها. تمت رؤية امرأة نيجيرية تبلغ من العمر 23 عامًا في قسم العيادات الخارجية الجراحية بالمركز الطبي الفيدرالي دوتسي بولاية جيغاوا بعد إحالة من قسم العيادات الخارجية العام بنفس المؤسسة ولديها تاريخ من انقطاع الطمث وزيادة الوزن المفرط والشعرانية لمدة عامين. كان الفحص السريري ملحوظًا بالنسبة لارتفاع ضغط الدم والمظهر الكوشينويدي. الى جانب ذلك، كان التقييم البيوكيميائي والإشعاعي يوحي بفرط كورتيزول الغدة الكظرية اليمنى. لقد خضعت لعملية استئصال الكظر اليمنى المفتوحة وخرجت من المستشفى بشكل مرضٍ وخالية من الأعراض مع متابعة سريرية كانت هادئة. لقد أبلغنا عن تجربتنا في الإدارة الناجحة لحالة نادرة من متلازمة كوشينغ الثانوية للورم الغدي الكظري